Comprehensive characterization of bioactive phenols from new Brazilian superfruits by LC-ESI-QTOF-MS, and their ROS and RNS scavenging effects and anti-inflammatory activity. (30th May 2019) - Soares, Jackeline Cintra; Rosalen, Pedro Luiz; Lazarini, Josy Goldoni; Massarioli, Adna Prado; da Silva, Camila Fortunato; Nani, Bruno Dias; Franchin, Marcelo; de Alencar, Severino Matias
Highlights: Phenolic compounds profile allowed the differentiation of distinct native fruits. The native fruits showed high scavenging activity for ROS and RNS. All native fruits showed anti-inflammatory activity in vivo . The in vivo toxicity showed that the fruits have a favorable low-toxicity profile. Based on their bioactivity, they can be considered as new Brazilian superfruits. Abstract: Brazilian native fruits (BNF) remain unexplored and underutilized resources with a high potential to improve human health and wellness. In our study, five new BNF ( Eugenia stipitata, Sageretia elegans, Byrsonima arthropoda, Spondias mombin and Rubus rosaefolius ) were evaluated for their phenolic composition by LC-ESI-QTOF-MS; and for their ROS and RNS scavenging effects (ROO, O2 −, NO, HOCl); in vivo anti-inflammatory activity (neutrophil migration); and in vivo acute toxicity in Galleria mellonella . Eighty-six phenolic compounds were identified, including hydroxybenzoic acids, hydroxycinnamic acids, flavonoids, anthocyanins and ellagitannins, several of which had never been reported in BNF. The BNF exhibited high antioxidant effects against biologically relevant radicals, and treated animals showed decreased neutrophil influx and NF-kB activation. Thus, these BNF are good sources of antioxidant and anti-inflammatory molecules that can be beneficial for human health as functional foods. Based on their bioactivity, they can be considered as new Brazilian superfruits.